Creativity in information systems research - Simonovič, Mojca (Economic and business review, 2024)
For more than six decades, creativity has been the cornerstone of diverse scientific disciplines, including psychology, sociology, and organizational behavior (OB) studies. Its fundamental role in guiding business prospects, driving development, and fueling economic growth has made it an essential research theme in many fields. Yet, despite its importance, scholars within the information systems (IS) discipline have highlighted the significant lack of attention paid to this concept in their research. The transformative role creativity plays in contemporary business environments, along with the ever-present need to innovate, compete, and grow, sparked our curiosity. Is creativity still an understudied area in the IS discipline, as it was 10 years ago? Our goal was not simply to examine the current state of creativity studies within the IS field, but to chart its evolution from 2010 to the present day. Through a comprehensive systematic literature review, we scrutinized papers from prestigious journals and proceedings of acclaimed conferences within the IS field. The findings map out the trajectory of creativity studies, yet also point to an emerging research gap. Accordingly, the paper provides invaluable insights into future research directions, emphasizing the need to fill the creativity studies void within the discipline of IS.
Keywords: economic analyses; ekonomske analize; informacijski sistemi; information systems; literature review; pregled literature; raziskave; research